Kewirausahaan di Era Digital Meningkatkan Kinerja Wirausaha Melalui Manajemen SDM di Era Digitalisasi - Harry Saptarianto; Anwar Yusuf Lubis; Veronica Ruth Rohani Siburian (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
In the ever-evolving digital era, entrepreneurship is required to adapt quickly to technological changes and market needs. The digitalization era provides both opportunities and challenges, especially in managing human resources (HR). The research method used is the literature review method, by evaluating and analyzing journals, e-books, and research that has been done before and is relevant to this research. Effective human resource (HR) management plays an important role in improving entrepreneurial performance with digitalization. Companies that are responsive to market needs can adopt HR technologies such as cloud-based management systems and data analytics. To conduct digital entrepreneurship, companies can take the right strategies, such as conducting market research, building strong digital branding, conducting promotions, and conducting regular analysis and evaluation.